Mentoring sebagai percakapan mendalam untuk menemukan panggilan menjadi pendeta - Munster, Cindy Cecilia Tumbelaka-van; Dawa, Mariani Febriana Lere (KURIOS, 2024)
This article is about the church's mentoring process for those who become her prospective pastors. There is a tendency for this mentoring process to be more directed towards coaching, where the church conveys more information that the prospective new pastor needs to pay attention to. However, mentoring requires a more profound vision to approach a minister, not only coaching but also a journey of inner clarity to understand better and experience the reality of "inner calling" within a prospective pastor. This process of inner clarity requires intersubjective conversations, which ultimately strengthen internal conversations that increasingly make people understand their existence better: where they come from, where they are going, and what their fundamental obligations are in the present. In this article, the â€œgoing on a journey of inner clarityâ€ method will be called currere. If this process could be fostered in the mentoring process, it would create a kind of personal curriculum thatâ€“â€“from the depths of one's existenceâ€“â€“will create sustainable self-formation that is authentic. This continuous self-formation will make one's pastorate continue to grow towards "increasingly becoming a charisma" and not merely a ministerial position.Â AbstrakTulisan ini adalah tentang proses mentoring yang dilakukan oleh pihak gereja bagi mereka yang menjadi calon pendeta. Kecenderungannya, proses mentoring ini lebih mengarah ke pembinaan, di mana pihak gereja lebih banyak mengalirkan informasi yang perlu diperhatikan oleh pihak calon pendeta baru. Akan tetapi, untuk mendekati autentisitas kependetaan, proses mentoring memerlukan visi yang lebih mendalam; bukan sekadar pembinaan, namun juga suatu perjalanan penjernihan batin untuk lebih memahami dan mengalami realitas â€œpanggilanâ€ di dalam diri seorang calon pendeta. Proses penjernihan batin ini memerlukan percakapan intersubjektif yang pada akhirnya memperkuat konversasi internal yang semakin membuat orang lebih memahami keberadaan dirinya, dari mana ia berasal, ke mana ia menuju, dan apa-apa yang menjadi ikatan-ikatan kewajiban riilnya pada masa kini. Dalam artikel ini, metode â€œmenempuh perjalanan penjernihan batinâ€ itu akan disebut currere. Jika proses ini dapat terbina secara teratur dalam mentoring, akan menciptakan semacam kurikulum personal yang â€“ dari kedalaman eksistensi seseorang â€“ membentuk formasi diri berkelanjutan yang bersifat autentik dan membuat kependetaan seseorang terus bertumbuh ke arah â€œsemakin menjadi karismaâ€, dan bukan semata-mata jabatan ministerial.